Primary repair of tetralogy of fallot and major aorto-pulmonary collateral arteries with suspected Noonan syndrome: A rare case - Heroe Soebroto; Erdyanto Akbar; Arief Rakhman Hakim (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Tetralogy of Fallot (TOF) is a congenital heart disease that includes ventricular septal defect (VSD), pulmonary stenosis (PS), right ventricular hypertrophy (RVH), and an overriding aorta. A cyanotic heart defect can develop aorto-pulmonary collateral (APCA) to supply underperfused pulmonary beds. Genetic syndromes can occur in 20% of patients with TOF. In developing countries, diagnosed genetic syndromes associated with heart defects have not been covered by health insurance, even though outcomes of primary repair remain unknown. This study reported a case of an 11-year-old boy with cyanosis since birth, dyspnoea on effort,  growth delays, learning problems, scoliosis,  micropenis, hypertelorism, exophthalmos, facial dysmorphism, cryptorchidism, and major aorto- pulmonary collaterals. The patient underwent an echocardiographic study. It showed VSD malalignment with overriding aorta of 48%, critical pulmonary stenosis, and size of pulmonary arteries that were favourable for primary repair. Cardiac catheterization showed classic Fallot with normal coronary arteries and major aortopulmonary collateral arteries (MAPCA) arising. The patient underwent percutaneous coil embolization just before surgery. There was a problem during induction, the anaesthetist found that it was hard to place the ETT because there was membrane-like covering the trachea. Next, a median sternotomy was conducted, and aortic cross-clamping was achieved. Right atriotomy was performed, and it provided exposure to the malalignment VSD. A longitudinal pulmonary arteriotomy was made to expose infundibular stenosis. Infundibulectomy was performed, and it reconstructed the MPA with a pericardial patch. The VSD was closed by using a PTFE patch. The patient was transferred to an ICU afterward. Post-operative echocardiography showed a good outcome, and 15 days after surgery the patient was discharged. It could be concluded that primary repair of TOF with MAPCAs and suspected Noonan syndrome was conducted successfully.